Factors influencing diabetes self-management among adults with type 2 diabetes mellitus in China - Ni Yang; Khemaradee Masingboon; Niphawan Samartkit (Belitung Raya Foundation, Indonesia, 2022)
Background: In China, the prevalence of Type 2 Diabetes Mellitus (T2DM) continues to rise, and Diabetes Self-Management (DSM) is generally suboptimal. Thus, identifying the factors influencing DSM in adults with T2DM is crucial for healthcare providers. Objectives: This study aimed to 1) describe DSM among adults with T2DM in Wenzhou, China, 2) examine the correlations between diabetes knowledge, perceived self-efficacy, fatalism, social support, and DSM, and 3) determine how much power of the correlated independent variables could predict DSM. Methods: This study adopted the cross-sectional design and included 108 adults with T2DM who were randomly selected from the outpatient clinic of a hospital in Wenzhou, China. Data were recruited using a demographic questionnaire, and standardized tools were utilized to determine the correlation between DSM, diabetes knowledge, perceived self-efficacy, fatalism, and social support. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. Results: 62% of participants had poor blood glucose control (HbA1c ≥8.0%) and suboptimal DSM. Significant factors related to DSM were diabetes knowledge (r = 0.594, p <0.001), perceived self-efficacy (r = 0.447, p <0.001), and social support (r = 0.312, p = 0.001). The regression analysis revealed that all variables significantly explained 38.2% of the variance in DSM among adults with T2DM. However, only diabetes knowledge and perceived self-efficacy significantly predicted DSM (β = 0.468, p <0.001; β = 0.184, p = <0.05, respectively). Conclusion: The findings indicated that increasing diabetes knowledge and perceived self-efficacy could help improve DSM in T2DM to ascertain the ultimate treatment outcomes. Nurses and healthcare providers should improve the ability of patients and their families to think critically and act autonomously.